Foreign language writing assessment and brazilian educational policies - de Oliveira, Luciana C.; Aranha, Solange [UNESP]; Zolin-Vesz, Fernando (Taylor & Francis, 2018)
Little is known about foreign language assessment in Brazil, and much less about foreign language writing assessment. This chapter addresses to what extent foreign language writing assessment has been included in Brazilian educational policy in Years 1-3 of high school. The authors examine and discuss an official document that guides the teaching and learning of foreign languages in Brazil, especially English and Spanish, and the guidelines to select school textbooks. The authors propose a framework for the inclusion of foreign language writing assessment for the Brazilian educational context and discuss principles of foreign language writing assessment that should guide assessment and instruction in high school classrooms.